Pengembangan Bahan Ajar IPA Terpadu pada Materi Energi dengan Pendekatan Kontekstual untuk Siswa Sekolah Menengah Pertama - I Gede Sumertadana; Supriyatman Supriyatman (Universitas Tadulako, 2021)
This study aims to develop integrated science teaching materials on energy materials with a contextual approach for junior high school students. The theme used in the teaching materials is the source of energy in life. This type of research is research and development (Research and Development) based on the steps of the ADDIE model. The research was conducted through the stages of analysis, design, development, implementation, and evaluation. The teaching materials developed were validated by material expert validators and media expert validators, then teaching materials were given to science teachers and 20 students to find out responses to the developed teaching materials. The data collection instrument in this study was a questionnaire/questionnaire with a Likert scale of 1-4. The subjects in this study were grade VII students. The results of the assessment of teaching materials developed by material experts were 3.60 categorized as